Individual, freedom and equality in the liberal thought and in Marx - Leão Rego, Walquiria Domingues (Universidade Estadual Paulista / UNESP, 2009)
This article pretends to realize a brief bibliographical balance about some categories of the Tocqueville, Stuart Mill and Bentham's thought in order to confront hem with the Marx's thought and pretends to make a reflexion about politics in each one of them.